The immunoglobulin A isotype of the Arabian camel (Camelus dromedarius) preserves the dualistic structure of unconventional single-domain and canonical heavy chains - Conca, Walter; Saleh, Soad M.; Al-Rabiah, Rana; Parhar, Ranjit Singh; Abd-Elnaeim, Mahmoud; Al-Hindas, Hussein; Tinson, Alexander; Kroell, Katharina Birgit; Liedl, Klaus Roman; Collison, Kate; Kishore, Uday; Al-Mohanna, Futwan (Frontiers in Immunology, 2023)
Introduction The evolution of adaptive immunity in Camelidae resulted in the concurrent expression of classic heterotetrameric and unconventional homodimeric heavy chain-only IgG antibodies. Heavy chain-only IgG bears a single variable domain and lacks the constant heavy (CH) γ1 domain required for pairing with the light chain. It has not been reported whether this distinctive feature of IgG is also observed in the IgA isotype. Methods Gene-specific primers were used to generate an IgA heavy chain cDNA library derived from RNA extracted from the dromedary’s third eyelid where isolated lymphoid follicles and plasma cells abound at inductive and effector sites, respectively. Results Majority of the cDNA clones revealed hallmarks of heavy chain-only antibodies, i.e. camelid-specific amino acid substitutions in framework region 1 and 2, broad length distribution of complementarity determining region 3, and the absence of the CHα1 domain. In a few clones, however, the cDNA of the canonical IgA heavy chain was amplified which included the CHα1 domain, analogous to CHγ1 domain in IgG1 subclass. Moreover, we noticed a short, proline-rich hinge, and, at the N-terminal end of the CHα3 domain, a unique, camelid-specific pentapeptide of undetermined function, designated as the inter-α region. Immunoblots using rabbit anti-camel IgA antibodies raised against CHα2 and CHα3 domains as well as the inter-α region revealed the expression of a ~52 kDa and a ~60 kDa IgA species, corresponding to unconventional and canonical IgA heavy chain, respectively, in the third eyelid, trachea, small and large intestine. In contrast, the leporine anti-CHα1 antibody detected canonical, but not unconventional IgA heavy chain, in all the examined tissues, milk, and serum, in addition to another hitherto unexplored species of ~45 kDa in milk and serum. Immunohistology using anti-CHα domain antibodies confirmed the expression of both variants of IgA heavy chains in plasma cells in the third eyelid’s lacrimal gland, conjunctiva, tracheal and intestinal mucosa. Conclusion We found that in the dromedary, the IgA isotype has expanded the immunoglobulin repertoire by co-expressing unconventional and canonical IgA heavy chains, comparable to the IgG class, thus underscoring the crucial role of heavy chain-only antibodies not only in circulation but also at the mucosal frontiers.